OPTIMIZING LOCAL POTENTIAL THROUGH TRAINING ON ECO-FRIENDLY DISHWASHING SOAP PRODUCTION FOR HOUSEWIVES IN RANDUSONGO VILLAGE, GERIH DISTRICT NGAWI REGENCY EAST JAVA - Dewi Astutik; Khusnul Isma Nuriza; Ari Susetiyo (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This community service program aims to improve the household economy of women in Randusongo Village, Gerih Sub- district, Ngawi Regency, East Java, through training on the production og environmentally friendly dishwashing soap. The training was designed to provide mother with practical skills that can be applied in daily life, especially in reducing household expenses, while at the same time encouraging environmentally responsible practices. The method used include socialization, demonstrations, and hand-on practice in the soap- making process. The result showed that participants were able to produce dishwashing soap independently with good quality and safe materials. This activity also enhanced participants’ knowledge and awareness that this program can help families save household expenses and foster a more eco-friendly lifestyle with in the community.